2023
DOI: 10.3390/toxics11010072
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and Methylmercury-Induced Neurotoxicity, Evidence from Experimental Studies

Abstract: MeHg is an environmental neurotoxin that can adversely affect the development of the nervous system. The molecular integrity of chromatin in the nucleus is an important target of MeHg. Low levels of MeHg trigger epigenetic mechanisms that may be involved in long-lasting and transgenerational neurotoxicity after exposure. Emerging evidence has shown that these mechanisms include histone modification, siRNA, and DNA methylation. The MeHg-induced inhibition of neurodifferentiation and neurogenesis are mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Rodent and C. elegans assays have demonstrated epigenetic alterations, including to histone modifications, directly induced by NaAsO 2 and meHgCl exposures, as well as in their offspring [ 71 , 72 , 73 , 74 , 75 , 76 ]. Multi-generational studies on zebrafish and mice have demonstrated the long-term effects of mercury exposure passed down for multiple generations, indicating the potential effects on the epigenome [ 77 , 78 , 79 ]. However, most of these studies were not specific to reproductive endpoints and did not compare different forms of arsenic and/or mercury.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent and C. elegans assays have demonstrated epigenetic alterations, including to histone modifications, directly induced by NaAsO 2 and meHgCl exposures, as well as in their offspring [ 71 , 72 , 73 , 74 , 75 , 76 ]. Multi-generational studies on zebrafish and mice have demonstrated the long-term effects of mercury exposure passed down for multiple generations, indicating the potential effects on the epigenome [ 77 , 78 , 79 ]. However, most of these studies were not specific to reproductive endpoints and did not compare different forms of arsenic and/or mercury.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of toxic metal poisoning in cattle also involves testing milk, an indirect indicator of environmental pollution (Pšenková et al, 2020). Toxic metals predominantly accumulate in internal organs making it feasible to establish standard levels in the body (Ke et al, 2023). Diagnosis and control of contamination in animal feed ensure the safety of human food and health.…”
Section: Monitoring Of Toxic Metals Contaminationmentioning
confidence: 99%
“…Further, Pb disrupts calcium signaling pathways by interfering with calcium-dependent processes that affects neurotransmitter release and synaptic plasticity ( Cory-Slechta et al, 2016 ). Hg impairs mitochondrial function and energy metabolism, causing cellular dysfunction and apoptosis ( Ke et al, 2023 ). Moreover, by disrupting neurotransmitter signaling, Hg interferes with the function of ion channels and neurotransmitter transporters, contributing to neurotoxicity ( Novo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, inorganic Hg in water and sediment can synthesize MeHg under the action of microorganisms [61]. The emerging evidence for Hg-induced toxicity is mainly neurotoxicity, reproductive toxicity, histone modification, siRNA and DNA damage, and methylation [62][63][64][65][66]. In addition, prenatal and postnatal exposure to Hg is significantly associated with testosterone levels and Tanner stage > 1 in children [67].…”
Section: Mercury (Hg)mentioning
confidence: 99%